The Effect of Talking Stick Type Cooperative Learning Model on the Mathematics Learning Outcomes of Grade III Students - Endang Manurung; Theresia Monika Siahaan; Osco Parmonganan Sijabat (CV Putra Publisher, 2026)
This research aims For Know The Influence of Learning Models Cooperative Talking Stick Types on Learning Outcomes Mathematics Grade III Students Uptd Sd Negeri 122399 Pematangsiantar. This research is studies quantitative as well as design pre-experimental, type design pre -test – post -test group. This design utilized because there is testing in form pre - test, implemented before treatment and post -test were given after treatment as well as utilizing working models The same Based on discussion in chapter this, researcher explain structure problems and hypotheses submitted as well as conclusion withdrawn start of study output obtained, then all over activity study discussed about impact of teaching models cooperative. Impact of teaching models cooperative towards teaching output Mathematics in Class III UPTD SD N 122399 Pematang Siantar is as as follows: Based on the output of the study by eye lessons in Class III UPTD SD N 122399 Pematang Siantar, the average pre-test score in content Mathematics